June 1941 Uprising in Kretinga, Mažeikiai and Telšiai Counties - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2010)
The topic of the article is the June 1941 Uprising in Kretinga, Mažeikiai and Telšiai counties. The work underlines that the Uprising emerged and the partisan squads were formed not spontaneously, since the underground participants in Kretinga, Mažeikiai and Telšiai counties, as in other localities of Lithuania, prepared for the Uprising and formed the armed partisan fighting forces in advance. It was determined that during the June 1941 Uprising in Kretinga County 16 partisan squads of rebels operated, 23 in Mažeikiai County, 14 in Telšiai County (in total 53 squads). All 16 squads in Kretinga County could have about 1248 partisans rebels, 14 Telšiai County squads about 1330, 23 Mažeikiai County squads about 1380 partisans rebels (in total 53 Kretinga, Mažeikiai and Telšiai squads – about 3958 rebels). The Uprising in those counties had its own specificities. Kretinga County was occupied very quickly by the German army; therefore here the partisans rebels participated in fighting actions against the Red Army and Soviet power activists already in the territory occupied by the Germans. The Germans occupied Telšiai and Mažeikiai counties somewhat later, therefore partisans rebels participated in the actions against Soviet activists and Red Army before the entry of the German Army. The rebels aimed at occupying the centres of the counties and rural districts and proclaiming their power. The rebels became enforced in Kretinga County without much difficulty, since it took place in the rear of the German Army. For the rebels in Mažeikiai and Telšiai counties it was more difficult to do this, since Soviet activists with the support of the Red Army opposed them. During the fights with the Red Army and Soviet activists, Mažeikiai County partisans rebels lost 22, Telšiai County partisans – 8 people (a total of 30 people). Partisans during the Uprising and after it in Kretinga County arrested more than 291, in Telšiai County more than 120, in Mažeikiai County over 67 Soviet power activists (in total over 478 activists). Partisans in Kretinga County arrested over 35, in Mažeikiai County over 180, in Telšiai County over 233 Soviet fighters (in total over 448 persons). In Mažeikiai County, from the hands of rebels fell over 30, in Telšiai County 3 Soviet soldiers (in total over 33 persons). No information exists about the Red Army soldiers that fell from the hands of the Kretinga partisans rebels, but archival data make it possible to presume about their existence here. This work also explores the relationship of the rebels in Kretinga, Mažeikiai and Telšiai counties with the holocaust. It was established that the resistance participants in Palanga and Kuliai rural districts of Kretinga County already during the June 1941 Uprising contributed indirectly to the Jewish genocide. No information exists about the participation of partisans rebels in Mažeikiai and Telšiai counties in the Jewish genocide during the June 1941 Uprising.